Internal marketing impact on business performance in a retail context - Panigyrakis, George G.; Theodoridis, Prokopis K. (My University, 2009)
Purpose: The majority of research pertaining to internal marketing (IM) is conceptual and still remains so even at present. The lack of widely accepted definitions of the IM concept and a relevant valid measure has lead to increased attempts by academia to investigate the relative concepts and measures. The purpose of this paper is to examine a synthesis of IM and investigates its effect on business performance in a retail context. Design/methodology/approach: The context of this paper is within supermarket chains in Greece with nation wide coverage. A survey is designed and implemented using the branch managers. Findings: SEM analysis indicates five dimensions of the IM construct: formal interaction, reward systems, feedback, internal procedures and policies and internal customer orientation (ICO). Retailers seem to adopt in an embryonic stage a concept of IM. IM indeed has a positive effect on business performance. Research limitations/implications: Single key informant, single context of the paper are considerations when examining research limitations. Practical implications: The embryonic stage of adopting and implementing IM within supermarket chains illustrates a certain manner of managing the internal customer; centralisation of procedures and tactics. Even if the concept of IM is partially exploited, the respective organisational behaviours clearly have a positive impact on both financial and non-financial aspects of retail performance, thus revealing their importance. Originality/value: This paper contributes to the rare empirical investigation of the IM notion in the firm and provides evidence on both its synthesis and its impact on business performance. The authors synthesize the concepts of internal market and ICOs providing a new approach to IM. Construct and research propositions have been axiomatic and in an only conceptual context until recently. © Emerald Group Publishing Limited.
Keywords: Business performance; Greece; Internal marketing; Retailing; Supermarkets